2004
DOI: 10.1128/jcm.42.10.4863-4865.2004
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the TechLab C. DIFF CHEK-60 Enzyme Immunoassay (EIA) in Combination with the C. difficile Tox A/B II EIA Kit, the Triage C. difficile Panel Immunoassay, and a Cytotoxin Assay for Diagnosis of Clostridium difficile -Associated Diarrhea

Abstract: Clostridium difficile-associated diarrhea (CDAD) is the most commonly identified cause of nosocomial diarrhea (10,12,17). The pathogenicity of C. difficile is due to the production of two exotoxins: toxin A, an enterotoxin, and toxin B. Both toxins A and B contribute to human disease (19).TechLab Inc. (Blacksburg, Va.) has recently marketed an enzyme immunoassay, C. DIFF CHEK-60, which detects glutamate dehydrogenase (GDH), a common C. difficile antigen (the assay is hereinafter referred to as TL-GDH), and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
80
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 22 publications
9
80
3
Order By: Relevance
“…The Tox A/B II assay demonstrated poor sensitivity (52.4%), near the lower end of the ranges reported by others compared to TC (66 to 88.6%) (6,8,13,20,27) or CCNA (38 to 90.7%) (8,13,20,32). The high specificity of the Tox A/B II assay of 97.5% is congruent with the work of others (95.7 to 100%) (6,8,13,20,27,32).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The Tox A/B II assay demonstrated poor sensitivity (52.4%), near the lower end of the ranges reported by others compared to TC (66 to 88.6%) (6,8,13,20,27) or CCNA (38 to 90.7%) (8,13,20,32). The high specificity of the Tox A/B II assay of 97.5% is congruent with the work of others (95.7 to 100%) (6,8,13,20,27,32).…”
Section: Discussionsupporting
confidence: 74%
“…They can detect glutamate dehydrogenase (GDH) (so-called common antigen) and/or major toxins A and B and are inexpensive, rapid, and easy to perform. A drawback of EIA toxin tests is a lack of sensitivity (8,9,13,15,16,20,22,27,30,32). Conversely, EIA GDH tests have good sensitivity but lack specificity, as they cannot distinguish toxigenic from nontoxigenic C. difficile (8, 13, 15, 23-25, 30, 32).…”
mentioning
confidence: 99%
“…This highlights the high negative predictive value of the GDH screen relative to culture, which has also been evaluated relative to CCNA (31,34,37). GDH screening is less specific, which may reflect antigenic homology among clostridia, as was suggested by a false-positive rapid stool toxin test result for a patient with Clostridium sordellii bacteremia (13).…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, Snell et al (22) demonstrated that using a two-step method in the diagnosis of C. difficile-associated diarrhea offered a marked increase in sensitivity compared to that of EIA alone. When using glutamate dehydrogenase (GDH) EIA followed by a toxin detection immunoassay for positive cases, the sensitivity was over 96% and reached 100% when a tissue culture cytotoxin assay was used for GDH-positive, toxin-negative cases (22).…”
Section: Discussionmentioning
confidence: 99%